Regional dependence in the timing of onset of rapid decline in Arctic sea ice concentration. Issue 12 (18th December 2015) - Close, S.; Houssais, M.‐N.; Herbaut, C.
Abstract: Arctic sea ice concentration from satellite passive microwave measurements is analyzed to assess the form and timing of the onset of decline of recent ice loss, and the regional dependence of the response. The timing of the onset is estimated using an objective method, and suggests differences of up to 20 years between the various subregions. A clear distinction can be drawn between the recent onset times of the Atlantic sector (beginning in 2003) and the much earlier onset times associated with the Pacific sector, where the earliest transition to rapid loss is found in 1992. Rates of decline prior to and following the transition points are calculated, and suggest that the postonset rate of loss is greatest in the Barents Sea, and weakest in the Pacific sector. Covariability between the seasons is noted in the SIC response, both at interannual and longer time scales. For two case regions, potential mechanisms for the onset time transitions are briefly analyzed. In the Barents Sea, the onset time coincides with a redistribution of the pathways of ice circulation in the region, while along the Alaskan coast, the propagation of the regional signal can be traced in the age of the sea ice. The results presented here indicate a series of spatially self‐consistent regional responses, and may be useful in understanding the primary drivers of recent sea ice loss. Key Points: Maps of the timing of transition in Arctic sea ice concentration are created Strong regional dependence is evident in the timing of transition Estimates of transition time show coherency between seasons